Transition blues: Sources of Stress among final year medical students approaching graduation - Osama Habib, M. Atif Qureshi, Khalid Mahmood, Monazza Javed, Azhar Ali Khan, Hafiz Hamad Asharaf, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: To assess the prevalence of the most common sources of stress among graduating final year medical students and to compare the students on gender and on a relative belonging to a medical profession. Methods: Students from two consecutive batches of final year MBBS were requested to complete a self-developed questionnaire about the various sources of stress. The study commenced from September 2018 to January 2020. Results were entered and analyzed in SPSS version 23. Descriptive statistics and independent samples T-test were used to analyze the data gathered. Results: A total of 194 (102 female, 92 male) final year MBBS class students participated in the study. The three most common sources of stress reported were; dealing with the practical life after graduation; encountering senior doctors as bosses and the highest expectations of their family/friends. Nearly two thirds of students reported high over stress levels. Female students were significantly more likely to report higher overall stress levels. On individual stress related items, females were significantly more likely to be stressed about the practical life ahead, about not feeling capable enough to deal with human life, about actual encounter with patients, and about encounter with senior doctors as their bosses. Students who had a parent or a sibling who was a doctor were significantly more likely to be stressed about the highest expectation of family friends. Conclusions: A significant number of final year medical students are highly stressed about the transition to working life. Female medical students are more likely to report overall stress as well as on particular stress related aspects of practical life and undergraduate training.